RETRACTED: Chen et al. Combined Effects of Artificial Surface and Urban Blue-Green Space on Land Surface Temperature in 28 Major Cities in China. Remote Sens. 2022, 14, 448 - Liang Chen; Xuelei Wang; Xiaobin Cai; Chao Yang; Xiaorong Lu (Remote Sensing)
The journal retracts the article “Combined Effects of Artificial Surface and Urban Blue-Green Space on Land Surface Temperature in 28 Major Cities in China” [...]